Om Linguatula arctica, reinens bihulmark - Haugerud, Rolf Egil (Rangifer, 1986)
Linguatula arctica, a newly described pentastomid species, is found in the nasal sinuses of the reindeer. It seems to cover the reindeer distribution. The prevalence in Norwegian reindeer herds is fairly high for an almost unknown parasite. L. arctica infects mostly calves. This led to the hypothesis that the reindeer mounts an immune response against the invader. The author discusses possible detrimental effects and proposes management efforts to control the parasite. Briefly, veterinary treatment is reviewed.